Emerging Trends and Impacts of Mobile Learning in Education: A Bibliometric Analysis - Yulia Fitri Ananda; Usmeldi; M. Giatman; Hansi Effendi (Postgraduate, University of Mataram, 2024)
This study aims to analyze the trend and impact of mobile learning in education through a bibliometric analysis approach. The method used is bibliometric analysis which involves statistical analysis of 690 publications related to mobile learning in education, collected from the Scopus database. The analysis process included the identification of the most influential publications, the most prolific journal sources, the leading authors, and the countries with the largest contributions. The results show that mobile learning is gaining increasing attention in academia, with a significant increase in the number of publications and citations over the 2019-2023 period. Leading journals and the most prolific authors have played an important role in advancing the discourse on mobile learning. The analysis also reveals emerging trends, such as the integration of mobile learning with augme nted reality technology and the importance of research in the context of higher education and developing countries. In conclusion, mobile learning has become a highly relevant topic in education, with great potential to change the way learning is done and increase the accessibility of education worldwide. This bibliometric analysis provides important guidance for future studies and practical implementation of mobile learning.